The role of external evaluation control mechanisms and the missing loop of innovation - Lídia Jesus Pecegueiro Serra; José Matias Alves; Diana Rafaela Soares (Journal of Pedagogical Research, 2023)
School accountability is transitioning and incorporating socioeconomic narratives regarding inclusion, responsiveness to societal challenges, improving performance, and continuous adjustments through innovation. Considering external evaluation mechanisms of regulation, this study provides evidence of the schools' lack of strategic orientations towards innovation that may leverage coherent and lasting improvements. A mixed research method was used to analyse 60 external evaluation reports concerning Portuguese school clusters. The study aims were to depict the school's strengths and improvement areas and identify associations between the school's organisational and pedagogical options that can promote or impede transformation. It used the odds ratio to quantify the associations' strengths and assess educational system practices. The results evidence that leadership and management appear as a robust valency in the Portuguese educational system, and self-evaluation and innovation are aspects of the school organisation that need to be developed and impactful. The findings also suggest that innovation appears as a missing loop when considering the external evaluation control mechanisms of action.